Optimizing Cognitive Learning Outcomes in Earth Science Through Online Process-Oriented Guided Inquiry Learning - Uy, Ricardo F.; Azuelo, Andrea G. (Asian Journal of Applied Education (AJAE), 2025)
This study examined the effects of online Process Oriented Guided Inquiry Learning (O-POGIL) on students’ cognitive learning outcomes in Earth Science. A one-shot pretest-posttest pre-experimental design was employed in the study. The reliable teacher-made test and an adapted academic self-concept survey questionnaire were the instruments used. Descriptive statistics, paired t-test and one sample t-test was used for statistical data analysis. Findings of the study revealed a satisfactory cognitive learning outcomes of students as exposed to O-POGIL. Further results indicated statistically significant difference on students’ cognitive learning outcomes on their pretest and posttest. Significant difference existed between students’ cognitive learning outcomes and the existing competency standard.